The Content Analysis of English Textbooks Based on Alan Cunningsworth’s Criteria: A Systematic Review - Agustinus Nai Aki; Mister G. Maru; Elisabeth Z. Oroh (Universitas Muhammadiyah Enrekang, 2024)
This investigation endeavors to elucidate the merits and demerits inherent in English textbooks as delineated in a myriad of scholarly articles dedicated to the content analysis of pedagogical materials for English instruction. A plethora of English textbooks, disseminated by governmental or non-governmental publishers, underwent scrutiny through the prism of various theoretical frameworks, most notably Alan Cunningsworth's discerning criteria. Employing a systematic review, this research meticulously unveils the commendable aspects and deficiencies encapsulated within the fabric of English textbooks or coursebooks expounded upon in the surveyed articles. A compendium of fifteen articles, spanning the temporal expanse from 2015 to 2023, was subjected to rigorous analysis through the discerning lens of Alan Cunningsworth's evaluative criteria. The discerning scrutiny revealed that all the scrutinized English textbooks impeccably adhered to and fulfilled the exacting standards posited by Cunningsworth's criteria. However, interspersed within these articles lay instances where certain textbooks failed to meet the stringent criteria delineated by Alan Cunningsworth. This investigation aspires to transcend its immediate findings, serving as a beacon of reference for future researchers and English educators engaged in the analytical or evaluative scrutiny of English instructional materials